2019
DOI: 10.1111/1471-0528.15804
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of amnioexchange for fetal gastroschisis

Abstract: Objective Morbidity in fetuses affected by gastroschisis is mainly the result of bowel ischaemic and inflammatory processes. Experimental studies on animal models show that clearing amniotic fluid from the digestive secretions by amnioexchange procedures reduces the inflammatory process. We evaluated the benefit of the amnioexchange procedure for fetal gastroschisis in humans. Design Prospective, interventional, randomised study. Setting Eight referral centres for fetal medicine. Population Pregnant women carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…In all these cases, however, long-term therapy with repeat amnioinfusions is almost always required. And, while amnioinfusions are relatively safe, the cumulative risk associated with repeated intrauterine access may pose unacceptable maternal morbidity [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all these cases, however, long-term therapy with repeat amnioinfusions is almost always required. And, while amnioinfusions are relatively safe, the cumulative risk associated with repeated intrauterine access may pose unacceptable maternal morbidity [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Amniotic fluid intervention is generally well tolerated, and contemporary data show it is relatively safe [17]. However, amnioinfusions are still susceptible to complications, and repeated intervention puts both the mother and fetus at risk [18][19][20]. A method for safe, chronic access would be ideal when repeat amniotic intervention is anticipated.…”
Section: Introductionmentioning
confidence: 99%
“…Animal models demonstrated a significant decrease in the presence of inflammatory mediators following amnioexchange, and so the procedure was attempted on human fetuses with gastroschisis. Unfortunately, the RCT was stopped early due to a higher fetal mortality rate in the amnioexchange arm, and interim results demonstrated that although there was an initial decrease in inflammatory and digestive compounds present within the amniotic fluid following the procedure, this effect was lost over time (31). Amnioexchange is not currently recommended as a potential treatment option for gastroschisis.…”
Section: Novel Therapiesmentioning
confidence: 99%
“…Although early reports appeared to show a significant reduction in postop curarization with amnioinfusion, 61 another case series 60 and a recent randomized controlled trial failed to demonstrate any significant benefit of this therapy. 63…”
Section: Amnioinfusion/amnioexchangementioning
confidence: 99%